Monte Carlo statistical methods - Robert, Christian P. (Array, 2004)
Sadržaj: 1. Introduction ; 2. Random variable generation ; 3. Monte Carlo integration ; 4. Controling Monte Carlo variance ; 5. Monte Carlo optimization ; 6. Markov chains ; 7. The Metropolis-Hastings algorithm ; 8. The Slice sampler ; 9. The two-stage Gibbs sampler ; 10. The multi-stage Gibbs sampler ; 11. Variable dimension models and reversible jump algorithms ; 12. Diagnosing convergence ; 13. Perfect sampling ; 14. Iterated and sequential importance sampling